Layered Ln(III) Complexes from a Sulfonate‐Based 1, 8‐Naphthalimide: Structures, Magnetism and Photophysics. Issue 6 (11th February 2019) - Carter, Anthony B.; Zhang, Ningjin; Kühne, Irina A.; Keene, Tony D.; Powell, Annie K.; Kitchen, Jonathan A.
Abstract: Five lanthanide(III) complexes of N ‐(4‐phenylsulfonate)‐1, 8‐naphthalimide (L1 ) are described {[Ln(L1 )(DMSO)5 (H2 O)2 ](L1 )2 ⋅3H2 O where Ln(III)=Eu(III) (1 ), Tb(III) (2 ), Dy(III) (3 ), Ho(III) (4 ) and Er(III) (5 )} . A structural, magnetic and photophysical study is reported for these complexes. The complexes feature a 1, 8‐naphthalimide based anionic ligand, which is known for extending structure directing properties through π‐based interactions. Within these complexes L1 acts as both a coordinating ligand as well as a non‐coordinating counter‐ion and overall the solid‐state structures adopt layered topologies that are achieved through π‐π interactions between L1 molecules. Complexes of 1 and 2 display the characteristic line‐like emission profiles expected for Eu(III) and Tb(III) whilst the magnetic properties of the Dy(III) containing complex 3 were investigated. Abstract : Luminescent supramolecular materials: π‐stacking and hydrogen‐bonding give rise to extended layered topologies in lanthanide complexes of a sulfonate‐naphthalimide ligand.